PROFILING COLLOCATION USE IN ENGLISH TEXTBOOKS FOR VIETNAMESE STUDENTS - Dung Thi Phuong Cao; Phuong Dzung Pho; Dang Nguyen Anh Chi (Universitas Sembilanbelas November Kolaka, 2021)
The study investigates (1) collocational profiles of an English textbook series for students from elementary to high schools in Vietnam, (2) the relevance of collocations targeted to high frequency collocation lists suggested in the literature, and (3) the recycling of the targeted collocations. An English corpus of 312,770 word tokens was built from the textbook series from which 13,292 collocations of verb-noun and 11,079 collocations of adjective-noun patterns were identified. The study found that frequencies of occurrences of collocation tokens and types increase from one grade level to another. Collocations targeted in the textbooks only cover 10.5% of the collocations recommended in an academic collocation list, and 31% were identified not high-frequency collocations. 76% of collocations are not recycled or recycled not to the point where learning is likely to occur. Implications for learning and teaching collocations and materials designing are discussed.